THE INTEGRATION OF HACCP AND HAS 23000 IN THE MEAT INDUSTRY TO ENHANCE AUDIT MANAGEMENT EFFECTIVENESS AND EFFICIENCY - Mishanty, Dhea Ana; Yola, Melfa; Anwardi, Anwardi; Harpito, Harpito; Hamdy, Muhammad Ihsan; Abdul Wahab, Mohamad Ikbar (Universitas Muhammadiyah Prof DR HAMKA, 2025)
Research aims: This study aims to design and validate an integration model between the Hazard Analysis Critical Control Point (HACCP) system and the Halal Assurance System (HAS) 23000 to enhance the effectiveness of internal audits at slaughterhouses while ensuring food safety and halal compliance. Design/Methodology/Approach: The research used a qualitative approach with the Expert Judgment method involving three experts (halal industry practitioners, industrial engineering academics, and halal quality management). The stages include: (1) mapping HACCP and HAS 23000 criteria, (2) designing an integration model based on the similarity of document functions and processes, (3) validation through a questionnaire with a scale of 1-9, and (4) feasibility analysis based on the percentage of scores. Research findings: The validation results indicate that the HACCP–HAS 23000 integration model falls into the Highly Suitable category (average 80.4%). his model aligns HACCP Critical Control Points (CCPs) and HAS 23000 critical activities within a unified audit framework, potentially enhancing efficiency, consistency in oversight, and the integrity of the halal supply chain. Theoretical Contribution/Originality: This study offers two innovations: (1) the first integration model specifically designed for NKV III slaughterhouses, (2) the application of Expert Judgment to align the scientific perspectives of HACCP and HAS 23000 sharia standards. Practitioners/Policy Implications: For RPH, this model has the potential to simplify internal audits and reduce document duplication. For BPJPH, it can be adopted as technical guidelines for halal certification for small-scale RPH. Globally, it offers a solution for countries with fragmented halal certification. Research Limitations/Implications: The study was limited to three expert respondents and focused on one slaughterhouse case. Future research should validate the model across multiple facilities and expand the expert panel. Long-term implementation studies are needed to assess practical effectiveness.